2003
DOI: 10.1038/sj.embor.embor861
|View full text |Cite
|
Sign up to set email alerts
|

MYC recruits the TIP60 histone acetyltransferase complex to chromatin

Abstract: The transcription factor MYC binds specific DNA sites in cellular chromatin and induces the acetylation of histones H3 and H4. However, the histone acetyltransferases (HATs) that are responsible for these modifications have not yet been identified. MYC associates with TRRAP, a subunit of distinct macromolecular complexes that contain the HATs GCN5/PCAF or TIP60. Although the association of MYC with GCN5 has been shown, its interaction with TIP60 has never been analysed. Here, we show that MYC associates with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
303
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(331 citation statements)
references
References 27 publications
24
303
2
2
Order By: Relevance
“…In agreement with its function in histone acetylation, Tip60 is mainly involved in transcriptional activation of specific genes (Gaughan et al, 2001;Berns et al, 2004;Legube et al, 2004). Transcriptional regulation of some genes, such as E2F or c-mycdependent genes, most likely involves the whole Tip60 complex (Frank et al, 2003;Taubert et al, 2004). However, it was recently shown that, on p21 promoter at least, Tip60 and p400 have antagonistic functions (Tyteca et al, 2006), with p400 functioning directly or indirectly as a repressor of Tip60 (meaning that p400 knockdown induces p21 expression in a Tip60-dependent way).…”
Section: Introductionmentioning
confidence: 89%
“…In agreement with its function in histone acetylation, Tip60 is mainly involved in transcriptional activation of specific genes (Gaughan et al, 2001;Berns et al, 2004;Legube et al, 2004). Transcriptional regulation of some genes, such as E2F or c-mycdependent genes, most likely involves the whole Tip60 complex (Frank et al, 2003;Taubert et al, 2004). However, it was recently shown that, on p21 promoter at least, Tip60 and p400 have antagonistic functions (Tyteca et al, 2006), with p400 functioning directly or indirectly as a repressor of Tip60 (meaning that p400 knockdown induces p21 expression in a Tip60-dependent way).…”
Section: Introductionmentioning
confidence: 89%
“…Myc recruits Tip60 to chromatin via the TRRAP subunit (Frank et al, 2003) and interacts with Pontin, thus regulating cellular growth and proliferation by gene repression (Bellosta et al, 2005). Moreover, Tip60 not only interacts with myc, but can also counteract myc as a haplo-insufficient tumour suppressor by modulating oncogene-induced DNA-damage response during lymphomagenesis in both mouse and humans (Gorrini et al, 2007).…”
Section: Functions Of Tip60mentioning
confidence: 99%
“…In this context, Pontin was identified as a component of different chromatin remodeling and modifying complexes including the Tip60, Ino80 and Uri complexes (for review see Gallant 2007). In addition, it has been shown that Pontin interacts with several transcription regulators like β-catenin, c-Myc and E2F1 and associates with the promoters targeted by these factors (Bauer et al 2000;Bauer et al 1998;Dugan et al 2002;Frank et al 2003;Taubert et al 2004;Wood et al 2000). Through its interaction with Hint1, Pontin modulates β-catenin mediated transcription in the canonical Wnt-signaling pathway and apoptosis (Weiske and Huber 2005;Weiske and Huber 2006).…”
Section: Introductionmentioning
confidence: 99%